1989
DOI: 10.1037/0278-7393.15.2.352
|View full text |Cite
|
Sign up to set email alerts
|

Summary knowledge of results for skill acquisition: Support for the guidance hypothesis.

Abstract: Summary knowledge of results (KR) involves the presentation KR for each of a set of trials (e.g., 10) only after the last trial in the set has been completed. Earlier, Lavery (1962) showed that, relative to providing KR after each trial, a 20-trial summary KR was detrimental to performance in a practice phase with KR present but was beneficial for a no-KR retention test. Using a relatively simple ballistic-timing task, we examined summary lengths of 1 (essentially KR after every trial), 5, 10, and 15 trials, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
186
2
11

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(208 citation statements)
references
References 21 publications
9
186
2
11
Order By: Relevance
“…In addition, more recent studies have also demonstrated benefits of training variability in contexts such as organisational learning (Schilling, Vidal, Ployhart, & Marangoni, 2003) and cognitive skills (Yechiam, Erev, & Gopher, 2001). But most of the benefits of training variability have been demonstrated in motor tasks rather than cognitive tasks, such as throwing objects at targets of different distances (Wulf, 1991), moving objects at different distances and speeds (Kelso & Norman, 1978), controlling the speed and accuracy of an apparatus through the motor movement of a handle (Schmidt, Young, Swinnen, & Shapiro, 1989), continuous pursuit tracking (Wulf & Schmidt, 1997), and the forehand drive in tennis (Douvis, 2005). In contrast to the supporting evidence for positive effects of training variability, evidence also indicates that learning is highly specific to the training conditions (specificity of training); that is, transfer is most effective when the conditions of transfer closely match the conditions of training.…”
Section: U N C O R R E C T E D P Rmentioning
confidence: 99%
“…In addition, more recent studies have also demonstrated benefits of training variability in contexts such as organisational learning (Schilling, Vidal, Ployhart, & Marangoni, 2003) and cognitive skills (Yechiam, Erev, & Gopher, 2001). But most of the benefits of training variability have been demonstrated in motor tasks rather than cognitive tasks, such as throwing objects at targets of different distances (Wulf, 1991), moving objects at different distances and speeds (Kelso & Norman, 1978), controlling the speed and accuracy of an apparatus through the motor movement of a handle (Schmidt, Young, Swinnen, & Shapiro, 1989), continuous pursuit tracking (Wulf & Schmidt, 1997), and the forehand drive in tennis (Douvis, 2005). In contrast to the supporting evidence for positive effects of training variability, evidence also indicates that learning is highly specific to the training conditions (specificity of training); that is, transfer is most effective when the conditions of transfer closely match the conditions of training.…”
Section: U N C O R R E C T E D P Rmentioning
confidence: 99%
“…Many studies have provided feedback for balance improvement of cerebrovascular accident patients 3,15) . The types of feedback reported are faded 28) , summary 29,30) , average 31) , bandwidth 32) , and frequency feedback 17) , and the frequency and provision of feedback has varied. However, these feedback methods did not encourage active participation of the learner.…”
Section: Discussionmentioning
confidence: 99%
“…Clariana, 2000;Kulhavy & Anderson, 1972;Schroth, 1992), which were explained from various learning hypotheses, e.g. : interference-perseveration (Hannafin & Reiber, 1989;Kulhavy & Stock, 1989); frequency of feedback (Kulik & Kulik, 1988); guidance (Lewis & Anderson, 1985;Schmidt et al, 1989); and from the mathemagenic perspective (Landauer & Bjork, 1978;Robins & Mayer, 1993).…”
Section: Timing Of Cueingmentioning
confidence: 99%
“…Clariana, 2000;Kulhavy & Anderson, 1972;Schroth, 1992), which were explained from various learning hypotheses, e.g. : interference-perseveration (Hannafin & Reiber, 1989;Kulhavy & Stock, 1989); frequency of feedback (Kulik & Kulik, 1988); guidance (Lewis & Anderson, 1985;Schmidt et al, 1989); and from the mathemagenic perspective (Landauer & Bjork, 1978;Robins & Mayer, 1993).It has been argued before (e.g., Derry & Lesgold, 1996;Van Merriënboer & Sweller, 2003) that these findings and explanations on timing of cueing are now in need of reexamination in more authentic contexts and highly interactive environments, where learners must receive or actively seek information to carry out more complex tasks within training programs of longer duration. We expect that the 'teachable moment' of cueing may not only Timing of Cueing 8 depend on task characteristics (e.g., more descriptive or more prescriptive content), but even more so on the characteristics of the individual learner.…”
mentioning
confidence: 99%